Spruelike Enteropathy Associated with Olmesartan: An Unusual Case of Severe Diarrhea - Stephanie E. Dreifuss; Yutaka Tomizawa; Nicholas J. Farber; Jon M. Davison; Adam E. Sohnen (Case Reports in Gastrointestinal Medicine)
A 64-year-old male with a history of hypertension presented with worsening diarrhea and 25-pound weight loss over the preceding three months. Prior screening colonoscopy was unremarkable, and the patient failed conservative management. On presentation, the patient had orthostatic hypotension associated with prerenal azotemia for which olmesartan (40 mg/day) was held. Initial workup for chronic diarrhea was essentially unremarkable. Then, EGD was performed with small bowel biopsy, which showed a moderate villous blunting and an intraepithelial lymphocyte infiltration. Celiac disease was excluded by negative conventional serology tests and the absence of clinical response to a gluten-free diet. In the interim, diarrhea became resolving without any other interventions, and clinical response was achieved even with gluten-containing diet. Two months later, he achieved a complete resolution of diarrhea and regained 20-pound weight. Spruelike enteropathy is a clinical entity manifested by chronic diarrhea and intestinal villous atrophy. Spruelike enteropathy associated with olmesartan as a cause of drug-induced diarrhea is rare, and it has been reported only in a case series to date. This case highlighted the importance for clinicians to maintain a high index of suspicion for olmesartan as a precipitant of spruelike enteropathy.